2015
DOI: 10.1016/j.rbo.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Estudo anatômico da inervação da cápsula do cotovelo

Abstract: r e v b r a s o r t o p . 2 0 1 5;5 0(6):673-679 w w w . r b o . o r g . b r Artigo original Estudo anatômico da inervação da cápsula do cotovelo ଝ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The elbow joint in M. tridactyla presented lateral deviation in the radiographic exam. The radius presented a lateral deviation, while the ulna presented a medial deviation, as it occurs in other Xenarthras, such as Tamandua (Cavalheiro et al, 2015; Scheidt et al, 2022), but also humans. This description seems different from sloths of the genus Bradypus , that have the ulna on a caudolateral position in relation to the radius and have a larger lateral epicondylus (Martins et al, 2022).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The elbow joint in M. tridactyla presented lateral deviation in the radiographic exam. The radius presented a lateral deviation, while the ulna presented a medial deviation, as it occurs in other Xenarthras, such as Tamandua (Cavalheiro et al, 2015; Scheidt et al, 2022), but also humans. This description seems different from sloths of the genus Bradypus , that have the ulna on a caudolateral position in relation to the radius and have a larger lateral epicondylus (Martins et al, 2022).…”
Section: Discussionmentioning
confidence: 65%
“…The elbow joint macroscopical assessment revealed that the capsule inserts into the radial fossa of the humerus in its proximal portion, as occurs in humans (Cavalheiro et al, 2015) but above the insertion described for domesticated species, which is proximal to the supratrochlear foramen, involving most of the radial fossa (Constantinescu & Constantinescu, 2009; König & Liebich, 2021). Distally, the capsule inserts near the radial head, extending medially until nearing the radial tuberosity and into the radial notch of the ulna, and the joint extends distally to constitute the proximal radioulnar joint, which resembles the description for carnivores (Constantinescu & Constantinescu, 2009).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation